Discourses of Institutionalization of Zakat Management System in Contemporary Indonesia: Effect of the Revitalization of Islamic Economics - Mari Adachi (International Journal of Zakat, 2018)
In Indonesia, zakat management was trying restructured in a top-down form based on the system followed in Malaysia and, in 1999, a related law was enacted. Although many previous studies have been conducted on zakat for its fundamental spiritual aspects and social roles, macroscopic research on its history of both theory and practice aspects is lacking. The transformation in the administrative reform of zakat, which focuses on not only the discourse of Islamic intellectuals but also the tone of the emerging Islamic economy and attitude of the management organization's practitioners and players, is important to understand the growth of Islam in Indonesia. This paper discusses how the zakat practice, which was an individual practice, expanded to include new objectives such as community development or financial inclusion without losing its original spiritual significance. Further, the paper clarifies how an institutionalized approach to zakat management helps in the development of new theoretical intervention areas and contributes to community development and empowerment, without compromising the original poverty alleviation programs. Keywords: Zakat management, Indonesia, Islamic economics